p(x) = p1(x) + p2(x) – 4p3(x) , если p1(x) = - 2x^2 + 3x; p2(x) = 4x^2 – 3; p3(x)=2x–4,то
p1(x) = 3x + -2x^2
p2 (x) = 4x^2-3
p3 (x) = 2x-4
p(x) = (4x^2-3) + (- 2x^2 + 3x) - 4(2x – 4)
p(x) = 2х^2 - 5х - 13
ответ: 2x^2-5x -13 =0
1) f'(x)=6x^2-6x-12;
f'(x)=0 <=> 6x^2-6x-12=0 |:6
x^2-x-2=0
x1=2 - не входит в промежуток в условии
x2=-1
f(-2)=-16-12+24+24=20
f(1)=2-3+12+24=35
f(-1)=-2-3+12+24=31;
ответ: minf(x)=f(-2)=20; maxf(x)=f(1)=35;
2) f'(x) = -sin2x*2+sinx*2
f'(x)=0 <=> 2sinx-2sin2x=0 |:2
sinx-sin2x=0; sinx-2sinxcosx=0; sinx(1-2cosx)=0; sinx=0 или cosx=-1/2;
x=pi * n, n принадлежит Z или x=+-2pi/3+2pi*k, k принадлежит Z;
f(-pi/3)=cos(-2pi/3) - 2cos(pi/3)=-1/2-2*1/2=-1/2-1=-3/2
f(pi)=cosx(2pi) - 2cos(pi)=1+2=3;
f(2pi/3)=cos(4pi/3)-2(2pi/3)=-1/2+2*1/2=-1/2+1=1/2;
ответ: minf(x)=f(-pi/3)=-3/2; maxf(x)=f(pi)=3;
1) f'(x)=6x^2-6x-12;
f'(x)=0 <=> 6x^2-6x-12=0 |:6
x^2-x-2=0
x1=2 - не входит в промежуток в условии
x2=-1
f(-2)=-16-12+24+24=20
f(1)=2-3+12+24=35
f(-1)=-2-3+12+24=31;
ответ: minf(x)=f(-2)=20; maxf(x)=f(1)=35;
2) f'(x) = -sin2x*2+sinx*2
f'(x)=0 <=> 2sinx-2sin2x=0 |:2
sinx-sin2x=0; sinx-2sinxcosx=0; sinx(1-2cosx)=0; sinx=0 или cosx=-1/2;
x=pi * n, n принадлежит Z или x=+-2pi/3+2pi*k, k принадлежит Z;
f(-pi/3)=cos(-2pi/3) - 2cos(pi/3)=-1/2-2*1/2=-1/2-1=-3/2
f(pi)=cosx(2pi) - 2cos(pi)=1+2=3;
f(2pi/3)=cos(4pi/3)-2(2pi/3)=-1/2+2*1/2=-1/2+1=1/2;
ответ: minf(x)=f(-pi/3)=-3/2; maxf(x)=f(pi)=3;
p(x) = p1(x) + p2(x) – 4p3(x)
p1(x) = - 2x^2 + 3x; p2(x) = 4x^2 – 3; p3(x) = 2x – 4.
р(х) = (- 2x^2 + 3x) + (4x^2 – 3) - 4(2x – 4)
р(х) = - 2x^2 + 3x + 4x^2 – 3 - 8х +16
р(х) = 2х^2 - 5х - 13
2х^2 - 5х - 13 = 0